Sex-based glass ceilings in US state-level bureaucracies, 1987-1997 - Reid, Margaret; Kerr, Brinck; Miller, Will (2004)
This study employed a national data set obtained from the U.S. Equal Employment Opportunity Commission (EEOC) to answer two questions. Are women adequately represented in the top-level positions in state bureaucracies and are impediments that women might encounter in reaching the highest level administrative posts related to the policy missions and/or organisational characteristics of these agencies? The authors found that (a) women are under-represented in top-level administrative and professional positions in distributive and regulatory agencies, suggesting the continued presence of glass ceilings in such agencies; (b) women are better represented among administrative and especially professional cadres in redistributive agencies, however their full representation at the uppermost administrative levels remains an unrealized goal; and (c) women are less well represented in higher paying positions (in proportion to their numbers in the agency) in agencies with higher salaries. - Reproduced.
Keywords: Bureaucracy; Women in the civil service